Control and constraint in e-learning choosing when to choose - Dron, Jon, 1961- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
Every learner is on a trajectory, an individual path that involves choices about what to do next in order to learn, choices that are bounded by intrinsic and extrinsic constraints. In some cases the learner controls those choices, sometimes they are made by someone or something else, sometimes control is negotiated, or it emerges from complex interactions of many agents. Control and constraint in e-learning: choosing when to choose pulls apart that simple dynamic, examines it in detail, and explores its consequences to provide a new, theoretically grounded approach to the design of e-learning systems, to the benefit of teachers, programmers, researchers and instructional designers alike. In addition to shedding new light on traditional e-learning systems, it demonstrates that the social technologies underpinning Web 2.0 are fundamentally different in their dynamics of control and, consequently, when designed and used with care, offer benefits that significantly exceed the promise of their forebears.